Pelanggaran Etika dan Integritas Hakim: Tinjauan terhadap Efektivitas Komisi Yudisial dan Badan Pengawas Yudisial - Rudiyansah, Muhammad Mas Davit Herman (Abdurrauf Law and Sharia, 2024)
The judicial institution is a cornerstone of the rule of law, with judges acting as central figures in the pursuit of justice. Judges are expected to perform their duties with utmost integrity, upholding their honor and dignity. However, rising incidents of ethical violations and abuse of power by judges in Indonesia have triggered public concern. The Judicial Commission (KY) and the Supervisory Body of the Supreme Court (MA) play critical roles in maintaining judicial integrity, tasked with supervising judges' behavior and performance. This study utilizes a case study approach, focusing on judges at the Surabaya District Court, to assess the effectiveness of oversight conducted by KY and MA. Using both juridical-normative and juridical-empirical research methods, the findings expose challenges in enforcing ethical codes, including limited resources, poor coordination, and ineffective sanctions. These violations reflect conflicts of interest and a lack of independence in judicial decisions. Recommendations include strengthening sanctions, enhancing transparency in supervision, and providing ethics education for judges. The active involvement of the community through reporting mechanisms is also encouraged to bolster the enforcement of justice. Keywords: Legal Supervision; Ethical Violations; Panel of Judges; Enforcement of Justice Abstrak: Lembaga peradilan merupakan tonggak utama penegakan hukum, dengan hakim sebagai tokoh sentral dalam upaya menegakkan keadilan. Hakim diharapkan dapat menjalankan tugasnya dengan integritas yang tinggi, menjunjung tinggi kehormatan dan martabatnya. Namun, maraknya pelanggaran etika dan penyalahgunaan wewenang oleh hakim di Indonesia telah menimbulkan kekhawatiran masyarakat. Komisi Yudisial (KY) dan Badan Pengawas Mahkamah Agung (MA) memegang peranan penting dalam menjaga integritas peradilan, yang bertugas mengawasi perilaku dan kinerja hakim. Penelitian ini menggunakan pendekatan studi kasus dengan fokus pada hakim di Pengadilan Negeri Surabaya untuk menilai efektivitas pengawasan yang dilakukan oleh KY dan MA. Dengan menggunakan metode penelitian yuridis-normatif dan yuridis-empiris, temuan penelitian mengungkap berbagai tantangan dalam penegakan kode etik, antara lain keterbatasan sumber daya, buruknya koordinasi, dan sanksi yang tidak efektif. Pelanggaran tersebut mencerminkan adanya benturan kepentingan dan kurangnya independensi dalam putusan pengadilan. Rekomendasi yang diberikan antara lain penguatan sanksi, peningkatan transparansi dalam pengawasan, dan pemberian pendidikan etik bagi hakim. Pelibatan aktif masyarakat melalui mekanisme pelaporan juga didorong untuk mendukung penegakan keadilan